New data on Belippo and Myrmarachne of Kenya (Araneae: Salticidae: Myrmarachninae) - Wesołowska, Wanda; Wiśniewski, Konrad (Zootaxa, 2015)
Basing on the collection of Åke Holm, we provide new data on African Myrmarachninae from Kenya: Belippo elgonensis sp. n. (♂) and B. terribilis sp. n. (♂) are described, as well as the previously unknown female of Myrmarachne giltayi. Belippo calcarata, B. milloti and M. dundoensis are recorded from Kenya for the first time and new records for Myrmarachne kiboschensis, M. lawrencei and M. marshalli are given.